Answer :

P(1) is true

Let us assume P(k) is true

= (k+1)

^{2}.

To prove P(k+1) is true using P(k)

P(k+1) =

= (k+2)

^{2}…………(1)

L.H.S of (1)

= (k+1)

^{2}

= (k+2)

^{2}

Which is the R.H.s of ……………. (1)

P(K+1) is true.

By the Principle of mathematical induction, P(n) is true for all values of n where n N

Hence proved.

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation